Manajemen Kesan Dosen Milenial di Panggung Digital dalam Interaksi dengan Mahasiswa Generasi Z - Eva Rufaida Rahman; Rini Rinawati; Oji Kurniadi (UPT Publikasi Ilmiah (Universitas Islam Bandung), 2025)
The interaction between Millennial Lecturers and Generation Z students has expanded beyond the classroom into digital spaces, particularly social media, where identity and professionalism are continuously negotiated. Despite this shift, limited research explores how lecturers manage impressions in these online environments. This study aims to examine how Millennial Lecturers perform impression management on digital stages, especially social media, and how it supports their on-campus image. Using a qualitative approach within the dramaturgical framework, data were collected through in-depth interviews, observations, documentation, and source triangulation. The findings reveal that lecturers consciously curate their digital presence to balance professionalism and approachability. Social media serves as a stage for self-representation and role negotiation that influences academic relationships. The study highlights self-awareness, communicative flexibility, and digital literacy as essential in sustaining positive academic and interpersonal impressions.